2019
DOI: 10.12998/wjcc.v7.i19.3082
|View full text |Cite
|
Sign up to set email alerts
|

How should congenital absence of cruciate ligaments be treated? A case report and literature review

Abstract: BACKGROUNDHypoplasia of bilateral cruciate ligaments is a rare congenital malformation. The diagnosis of such diseases and indications for the various treatment options require further analysis and discussion.CASE SUMMARYThe patient is a 26-year-old Chinese woman who has been suffering from knee pain since the age of 8 years, 2-3 episodes a year. Three years ago, due to the practice of advanced yoga poses, the frequency of left knee pain increased, requiring prompt medical treatment. Magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Some authors recommend conservative treatment as many patients may not have any symptoms, as they may have adapted to these developmental abnormalities. 9,18 Other studies have reported favorable outcomes with ACLR for symptomatic patients. One of the largest series was reported by Sachleben et al 12 from the Boston Children's Hospital, Boston, MA, USA.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Some authors recommend conservative treatment as many patients may not have any symptoms, as they may have adapted to these developmental abnormalities. 9,18 Other studies have reported favorable outcomes with ACLR for symptomatic patients. One of the largest series was reported by Sachleben et al 12 from the Boston Children's Hospital, Boston, MA, USA.…”
Section: Discussionmentioning
confidence: 98%
“…Based on a review of previous publications, 31% of patients start experiencing pain and instability due to mild trauma. 9 Isolated case reports have also indicated that patients with this disorder might progress to earlier knee osteoarthritis. 10,11 Given the rarity of the condition and wide spectrum of malformation, there is still no consensus regarding the optimal treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, congenital absence of cruciate ligaments shows similar defects, and the patients acquire osteoarthritis at later ages [41,42]. As Vcan complete knockout mice are embryonic lethal due to cardiac defects, Vcan is unlikely to be associated with this disease.…”
Section: Plos Onementioning
confidence: 99%
“…Reviewing the literature, a few articles were published to discuss aplasia or hypoplasia of the cruciate ligaments (3)(4)(5)(6)(7)(9)(10)(11). Up to date, no previous case was available in the literature, demonstrating aplasia of the posterior cruciate ligament in a young patient.…”
Section: Introductionmentioning
confidence: 99%